Analisis Efisiensi Penggunaan Modal Kerja Perusahaan Dengan Rasio Keuangan (Studi Kasus Pada PT. Bank Rakyat Indonesia Tbk., Periode 2014-2019) - Mailani Rabiulkhri; Nourma Wulanda; Maizar Santoni (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2022)
For banking companies, large assets provide advantages or benefits large amount of which in its use as working capital is required management policy keeping in mind the precautionary principle that is always applied banks in running their business. This study aims to analyze the efficiency the use of the company's working capital with financial ratios at PT Bank RakyatIndonesia Tbk. The method or analysis technique used is research quantitative descriptive, namely analyzing the results of the ratio in the financial statements the company then performs an analysis, description or interpretation of the data. The results of the study stated that the use of working capital at PT Bank Rakyat Indonesia Tbk for the 2014-2019 period has been efficient in terms of performance achievements companies that are still able to maintain financial ratios are in very good criteria. Large working capital and high liquidity generally will affect the decline in profit, therefore PTBank Rakyat Indonesia as the bank with the largest assets is required to always provide the best and satisfactory performance for each stakeholder which exists.